Vol.1 - H C Verma (New Delhi, 2024)
"Dr. Verma's book has been divided into two parts because of the size of the manuscript. It is a totally different attempt to teach physics, and it will be extremely useful to the undergraduate students. The exposition of each concept is extremely lucid. In carefully formatted chapters, besides problems and short questions, a number of objective questions have also been included. This book can certainly be extremely useful not only as a textbook, but also for preparation of various competitive examinations." Y. R. Waghmare, Professor of Physics, IIT Kanpur
English
Keywords: Gravitation; Kinematics; New ton's Law; Physics